Improving management of student clinical placements: insights from activity theory. Issue 1 (December 2016) - O'Keefe, Maree; Wade, Victoria; McAllister, Sue; Stupans, Ieva; Burgess, Teresa
Abstract Background An approach to improve management of student clinical placements, the Building Teams for Quality Learning project, was trialed in three different health services. In a previous paper the authors explored in some detail the factors associated with considerable success of this approach at one of these services. In this paper, the authors extend this work with further analysis to determine if the more limited outcomes observed with participants at the other two services could be explained by application of activity theory and in particular the expansive learning cycle. Methods Staff at three health services participated in the Building Teams for Quality Learning project: a dental clinic, a community aged care facility and a rural hospital. At each site a team of seven multi-disciplinary staff completed the project over 9 to 12 months (total 21 participants). Evaluation data were collected through interviews, focus groups and direct observation of staff and students. Following initial thematic analysis, further analysis was conducted to compare the processes and outcomes at each participating health service drawing on activity theory and the expansive learning cycle. Results Fifty-one interview transcripts, 33 h of workplace observation and 31 sets of workshop field notes (from 36 h of workshops) were generated. All participants were individually supportive of, and committed to, high quality student learning experiences. As was observed with staff at the dental clinic, a number of potentially effective strategies were discussed at the aged care facility and the rural hospital workshops. However, participants in these two health services could not develop a successful implementation plan. The expansive learning cycle element ofmodeling and testing new solutions was not achieved and participants were unable, collectively to reassess and reinterpret the object of their activities. Conclusion The application of activity theory and the expansive learning cycle assisted a deeper understanding of the differences in outcomes observed across the three groups of participants. This included identifying specific points in the expansive learning cycle at which the three groups diverged. These findings support some practical recommendations for health services that host student clinical placements.